1999
DOI: 10.1121/1.425555
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between computer simulations of room acoustical parameters and those measured in concert halls

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The models made simplify the interior space, eliminating any elements which, due to their smaller size, are not decisive when it comes to obtaining adequate results. However, the acoustic properties of the materials of the different surfaces (absorption and scattering) are more decisive for obtaining adequate results [26]. The environmental conditions (humidity and temperature), as well as the background noise obtained from in situ measurements, were considered for the simulations with TUCT algorithm 2 ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…The models made simplify the interior space, eliminating any elements which, due to their smaller size, are not decisive when it comes to obtaining adequate results. However, the acoustic properties of the materials of the different surfaces (absorption and scattering) are more decisive for obtaining adequate results [26]. The environmental conditions (humidity and temperature), as well as the background noise obtained from in situ measurements, were considered for the simulations with TUCT algorithm 2 ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…The comparison of results in Table 1 is also presented in terms of relative error [45,46] considering the Just Noticeable Difference (JND) of each parameter. In psycho-physics the JND is the smallest difference in sensation that a hearer can perceive.…”
Section: Different Spacesmentioning
confidence: 99%
“…2 This development in digital tectonics has so far primarily been the case in connection to the structural aspects of building but it might apply to other fields such as room acoustics. Several studies have shown the reliability of simulation programmes for calculation of room acoustic parameters 3,4 and recently isolated attempts have been made to explore the possibility of using computer programming in the initial design stages. One of these attempts is the programme ACOUSALLE, 5 which can support decisions in the first phases of the design but which, for the time being, is limited to operating with shoebox room shapes.…”
Section: Introductionmentioning
confidence: 99%